Characterization study of flax/strontium titanate/ polypropylene composite for low-k dielectric applications - Hari, Prashanth P.V.S; Elammaran, Jayamani; Soon, Kok Heng; Md. Rezaur, Rahman; Muhammad Khusairy, Bakri (Wiley Periodicals, LLC., 2021)
This study demonstrates the characterization of flax fiber reinforced polypropylene-strontium titanate composite and dielectric study for low-k dielectric applications. The composite was studied through thermal, morphological, and compositional aspects. Thermogravimetry analysis, differential scanning calorimetry shows a higher thermal stability with low glass transition temperatures and lowered decomposition temperatures of 375C. The morphological study on the surface of this composites had revealed closely packed layers of fiber, ceramic and polymer matrix, which deduces the increased dielectric constants between 3.92 and 4.25 after the addition of strontium titanate. The dielectric constant was found to be significantly higher with a 78% increase with strontium titanate inclusion at relaxation frequencies between 1 kHz and 2 MHz, respectively. Besides, the dielectric property data showed that dielectric permittivity of 4.2 (low k) with the inclusion of natural fibers and ceramic at higher frequencies and lowered corresponding dielectric losses. The infrared spectroscopy results also show a reduction in hydroxyl groups and confirms the presence of bonds that are subjected to high interfacial bonding.